A cleaner processing approach for cellulose reinforced thermoplastic polyurethane nanocomposites - Khairatun Najwa, Mohd Amin; Chaleat, Celine; Edwards, Grant; Martin, Darren J.; Pratheep Kumar, Annamalai (John Wiley and Sons Inc, 2022)
In a manner of addressing challenges in scalable processing of thermoplastic polyurethane (TPU) nanocomposites through extrusion methods, this study reports a very clean processing approach of incorporating cellulose nanocrystal (CNC) into a TPU matrix, with no acid or organic-solvents usage. It involves a mechanical deconstruction of microcrystalline cellulose (MCC) into nanoscale particles in water and polyol through scalable bead-milling, vacuum drying, and followed by twin-screw reactive extrusion with isocyanate and chain extender. The thermal stability of CNC was higher than that of typically acid-hydrolyzed CNC and suitable for processing with the precursors of TPU at typical processing temperature range (175–190°C). The CNC incorporation at very low loadings (0.5, 0.8 wt%) through this methodology resulted in substantial enhancements in tensile properties (for example, up to 28% in strength and toughness) without any significant stiffening effect. Moreover, the nanocomposites retained elastic properties, including elongation at break (%), resilience, and creep resistance. Their chemical properties and thermal transitions were also found to support the retained thermoplastic behavior while improving mechanical performance.